Eksperimental'noe obosnovanie effektivnosti metoda igrovych zadac v processe individual'noj techniko-takticeskoj podgotovki junych basketbolistov - Germanov, G. N.; Rodin, A. V.; Pavlov, E. A.; Voitovich, D. I. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2014)
In this article for the first time from a position of complex researches justification of a pedagogical technology of improvement individual technical and tactical actions of young basketball players on the basis of a method of game tasks is given. On the basis of method of game tasks, conducted in an interactive way, the authors reveal the contents of the pilot program and provide evidence confirming the high efficiency of individual tactical training of young basketball players.